Advances of nanotechnology for intracerebral hemorrhage therapy - Wang, Jiayan; Wang, Tianyou; Fang, Mei; Wang, Zexu; Xu, Wei; Teng, Bang; Yuan, Qijuan; Hu, Xin (Frontiers in Bioengineering and Biotechnology, 2023)
Intracerebral hemorrhage (ICH), the most devastating subtype of stoke, is of high mortality at five years and even those survivors usually would suffer permanent disabilities. Fortunately, various preclinical active drugs have been approached in ICH, meanwhile, the therapeutic effects of these pharmaceutical ingredients could be fully boosted with the assistance of nanotechnology. In this review, besides the pathology of ICH, some ICH therapeutically available active drugs and their employed nanotechnologies, material functions, and therapeutic principles were comprehensively discussed hoping to provide novel and efficient strategies for ICH therapy in the future.